Kant e Hölderlin: da reflexão estética ao pensamento poético - Pasqualatto, Tamara Havana dos Reis (2017)
The relation between philosophy and poetry, showed by Kant in the Critique of Judgment, became the motivation to the thoughts of Friedrich Hölderlin, one of the first moderns poets-philosophers. Due to that, the aim of the presente work is to relate both authors: the philosopher and the poet. Each of them themed the aesthetic their way. Kant did it considering the reflective aspect while Hölderlin considered the perspective of poetic thought as produtive capacity. In order to demonstrate some specific differences between the projects of each author, we’ve exposed kantian’s and hölderlinian’s theories separately. At the beginning we themed the aesthetic foundation of the first and third Kant’s Critique to make explicit the activities of the faculty of the determinative and reflective judgment, through which the argumentation will be built regarding art’s foundation, and the poetry as occupying “the highest position”. On the other hand, in Hölderlin’s aesthetic project, we presented the way from the art’s theoretical assumptions taken out from Kant to the new emphasis the poet gives to the creative activity, producer of poetic genius that, due to the concession of more freedom to the faculty of imagination, exceed what the genius was able to do in Kant’s conception. We conducted a brief presentation of the novel Hyperion by Hölderlin to illustrate this creative ability of the poetic thought. That work, for being inserted in the context of German Idealism, dialogues with the problems discussed during this period. Without intent to a theoretical speculation, Hölderlin poetically shows his conclusions over the task of unification of the oppositions between subject and object, nature and freedom, etc. He can, thus, produce a aesthetic solution that is expressed on the eccentric path’s image lived by the novel’s character, through which he reachs, after some experiences, the dissolution of dissonances, the harmony between nature and freedom, being able to unify the oppositions manifested in it.